Posted by **hunter** on Wednesday, July 3, 2013 at 5:35pm.

Solve the following system using the substitution method:

6x - 2y = -4

y = 3x + 2

- algebra -
**Reiny**, Wednesday, July 3, 2013 at 8:41pm
sub the 2nd into the 1st:

6x - 2(3x+2) = -4

6x - 6x - 4 = -4

-4 = -4

infinite number of solutions, just use the 2nd, pick any x you feel like, and get the y

e.g.

x = 2

y = 3(2)+2 = 8

etc

What you really have is the same equation twice.

(multiply the 2nd by 2 and you will get the 1st)

## Answer This Question

## Related Questions

- algebra - Solve the following system using the substitution method: 3x + y = -3 ...
- Algebra - Solve the following system of equations using the substitution method:...
- Substitution Method-Plz help - Use the Substitution method to solve the system ...
- algebra - What is the solution of the system? Solve the system of equations ...
- algebra - solve the system of equations using the substitution method 8x - 9 = y...
- algebra - solve the system of equations using the substitution method 8x - 9 = y...
- Algebra 1 - solve the system of equations using the substitution method. 8x-9=y...
- math - Solve the following system using the substitution method: 2x + 4y = 5 x...
- math - Solve the following system using the substitution method: y = 3x - 9 y...
- Algebra Help Please - solve the system of equations using the substitution ...

More Related Questions